Identifikasi Faktor Penyebab Terjadinya Konflik Satwa dengan Masyarakat Desa Penyangga di Taman Nasional Kelimutu - Fandham Junior Bekalani; Fadlan Pramatana; Yusratul Aini (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This study aims to identify the factors and impacts that cause conflicts between wildlife and communities in buffer zones in Kelimutu National Park, analyze community perceptions, and determine the types of wildlife that often cause disturbances. Conflicts between wildlife and humans are increasing because wild animals often damage agricultural land and cause economic losses. The research was conducted in six buffer zone villages through purposive sampling of 93 respondents. Data were collected through interviews and observations and then analyzed descriptively and using a Likert scale. The results showed that the factors causing conflict were triggered by the degree of wild animals' preference for certain types of plants and forest encroachment. The impact experienced by the community was economic losses due to animals damaging their agricultural crops. The types of animals include wild boars (Sus scrofa), long-tailed macaques (Macaca fasciularis), porcupines (Erinaceinae), large rats (Bandicota bengalensis), and civets (Paradoxurus hemaphroditus). The entire community has a positive perception of the existence of these animals for the balance of a sustainable ecosystem.